2021
DOI: 10.2147/ott.s314810
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene Protects Cisplatin-Induced Renal Injury in Mice via Inhibiting Oxidative Stress

Abstract: Purpose Cisplatin is one of the most widely used antineoplastic drugs but has limited therapeutic effects due to nephrotoxicity. The aim of this study was to determine the possible renoprotective effect of the antioxidant raloxifene on cisplatin-induced nephrotoxicity in mice. Materials and Methods Cisplatin-induced acute renal injury was established in female C57 mice that were treated with saline (normal control) or raloxifene over a 7-day period. The body weight of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Additionally, inflammation and apoptosis were responsible for CIS-induced renal damage [36]. Our findings were consistent with their results, as MDA levels were among the increased oxidant parameters in CISadministered rats [37,38]. Furthermore, a study examining the antidiabetic effect of RAN demonstrated a significant decrease in MDA levels in pancreatic tissue [39].…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, inflammation and apoptosis were responsible for CIS-induced renal damage [36]. Our findings were consistent with their results, as MDA levels were among the increased oxidant parameters in CISadministered rats [37,38]. Furthermore, a study examining the antidiabetic effect of RAN demonstrated a significant decrease in MDA levels in pancreatic tissue [39].…”
Section: Discussionsupporting
confidence: 90%
“…This result contrasts with previously published data demonstrating the antioxidative features of raloxifene (1), indicating the dual nature of raloxifene depending on cell specificity. 50,51 Concurrently with the observed increase in the granularity of the cellular cytoplasm through flow cytometry, supravital staining of the same cell line with acridine orange after a 72-hour treatment with raloxifene (1) or bipyraloxifene (2) resulted in a significant augmentation in the presence of autophagosomes, indicating a heightened autophagic process in response to the treatment (Fig. 3A).…”
Section: Flow Cytometrymentioning
confidence: 64%
“…This result contrasts with previously published data demonstrating the antioxidative features of raloxifene ( 1 ), indicating the dual nature of raloxifene depending on cell specificity. 50,51…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the body and kidney weights of rats from all groups were observed and renal index (%) was calculated according to the formula: (kidney weight/total body weight) × 100 33 .…”
Section: Methodsmentioning
confidence: 99%